Experimental and theoretical studies on the shear performance of innovative box-shape FRP profile-concrete hybrid beams. (December 2020) - Zhang, Pu; Liu, Xuan-Yu; Li, Qi-Long; Deng, En-Feng; Gao, Dan-Ying; Zhang, Zhe; Sheikh, Shamim Ahmed
Abstract: FRP-concrete hybrid beams have the advantages of good flexural stiffness, high load bearing capacity and excellent corrosion resistance. An innovative box-shape FRP profile-concrete hybrid beam was proposed and evaluated through experimental and theoretical studies in this paper. The shear capacity, deformation and interface slip of the hybrid beams were investigated through four-point bending tests. Two box-shape FRP profile beams and five box-shape FRP profile-concrete hybrid beams were tested. Three types of interfacial connections–wet bonding (WB), FRP shear key (SK) and FRP shear key combined with wet bonding (SK-WB) were considered in the five box-shape FRP profile-concrete hybrid beams. The failure mode, load–displacement relationship, load-slip relationship, strain distribution and load bearing capacity of the hybrid beams were observed and discussed in detail. The test results showed that the SK-WB interface had the best anti-slip effect among the three interface interfacial connections of the hybrid beams. The mechanical performance of the box-shape FRP profile-concrete hybrid beam was better than that of the box-shape FRP profile beam. The CFRP sheets significantly improved the shear resistance when used for the shear strengthening of the box-shape FRP profile-concrete hybrid beams. Formulas for predicting the mid-span deflection and shear capacity of the box-shape FRP profile-concrete hybrid beams were also derived and validated based on the plane-section assumption. The accuracy of the theoretical formulas was verified by comparing the theoretical results with the experimental ones.